G338(P) Child and parent perceptions and preferences for staff uniform in the paediatric emergency department. (May 2019) - Clarke, AM; Lyttle, MD; Marlow, RD
Abstract : Aims: Considering a change in departmental uniform we set out to determine what professional attire are preferred by children and parents for paediatric emergency department staff, and what impressions are created by different clothing. We also sought opinions about how clinicians' names and roles are best conveyed through their uniform, and what children and parents' priorities were with respect to staff's appearance. Methods: We carried out semi-structured small group interviews of a representative sample of children and their parents in the waiting room of our large tertiary paediatric emergency department. Participants were signposted to discuss key areas and asked their opinion of images of different clinical uniforms of doctors and nurses, dressed either in shirts, blouses, nursing tunics or scrubs. They were asked the relative ease and importance of visual aids for ascertaining clinicians' names and roles, using badges, embroidered scrubs and printed lanyards. Lastly, groups were asked their personal priorities for uniforms, including whether they should denote grade or role. All interviews were analysed thematically and for common key descriptors. Results: Of 37 participants surveyed, the majority of both adults and children preferred doctors to wear more traditional professional attire, such as a shirt rather than scrubs. The most commonly used key descriptors in response to this image were 'professional' and 'smarter', however images of doctors wearing scrubs were also well-received as 'friendlier' and 'less formal'. Nurses were slightly preferred to wear scrubs over tunics. Scrubs were most often described as 'more practical' and 'more comfortable', however some respondents found scrubs difficult to distinguish from other hospital staff and found tunics to be 'smarter'. Clinicians' names were considered easiest to read on lapel badges rather than lanyards, and photograph boards of staff in the waiting room were overwhelmingly supported. Conclusions: Parents and children wanted uniforms to be colourful and bright, and helpful to distinguish role. These findings are useful in future decisions about staff attire and in better orientating families within the emergency department.